Integrasi Taksonomi Bloom Digital Dalam Evaluasi Kompetensi Spiritual Dan Kognitif Peserta Didik Pada Pembelajaran Pendidikan Agama Islam - Jupri Jupri; Andi Fitriani Djollong; Irma Irma; Jumawati Jumawati; Muhammad Afit Imran (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The development of digital technology has transformed the paradigm of Islamic Religious Education (PAI) learning, including the evaluation of students' spiritual and cognitive competencies. One relevant approach in this context is the application of Bloom's Digital Taxonomy, which is a development of the classic Bloom's Taxonomy with adaptations to 21st-century skills. This literature review aims to analyze the integration of Bloom's Digital Taxonomy in Islamic Religious Education (PAI) learning evaluation, specifically in comprehensively assessing students' spiritual and cognitive competencies. The research was conducted through a literature review of various national and international scientific sources relevant to the themes of digitalization of learning, authentic assessment, and character education based on Islamic values. The results indicate that Bloom's Digital Taxonomy provides a systematic framework for developing evaluation instruments that involve higher-order thinking skills and the appreciation of spiritual values. Through the use of digital media such as reflective apps, da'wah vlogs, or e-portfolios, PAI teachers can assess students' analytical, synthesis, and evaluation skills while also observing their spiritual development. This integration requires teachers to be creative, innovative, and technologically literate so that assessments emphasize not only cognitive aspects but also facilitate the holistic development of students' character and faith.